The Effectiveness of Pronunciation Coach 3D Application in Enhancing Students’ Ability in Pronouncing Interdental Sounds - Cindy Cynthia Anastasya Zees; Mukrim Mukrim; Darmawan Darmawan; Rofiqoh Rofiqoh; Simon Moxon (e-Journal of ELTS (English Language Teaching Society), 2026)
This study aimed to determine whether the use of Computer-Assisted Pronunciation Training (CAPT), a software named Pronunciation Coach 3D, was effective in enhancing students' ability to pronounce interdental sounds at SMA Al-Azhar Mandiri Palu. This research was initiated by the preliminary research that showed students’ difficulties in pronouncing interdental sounds (/θ/ and /ð/), which are uncommon in Bahasa Indonesia as their native language. This study used a quasi-experimental design involving two groups: an experimental group and a control group, each consisting of 26 students. The experimental group was taught using Pronunciation Coach 3D, while the control group received conventional instruction. Data were collected through tests: pre-test and post-test, then analyzed using descriptive and inferential statistics, including the Wilcoxon Signed Rank Test and the Mann-Whitney U Test. The results showed that both groups improved. The average score of the experimental group increased from 57.40 to 90.38, while the control group increased from 71.35 to 82.88. The Wilcoxon test showed a statistically significant difference between pre-test and post-test scores in both groups (p < 0.05). Furthermore, the Mann-Whitney U test (p = 0.050) showed a marginal difference between the two groups. The effect size (r ≈ 0.27) indicated a small effect. It can be concluded that Pronunciation Coach 3D is effective in enhancing students' pronunciation skills, although the impact is not substantially higher than conventional teaching methods.